Primary CNS vasculitis: insights into clinical, neuropathological, and neuroradiological characteristics - Sheikh, Tahani Saker; Rozenberg, Ayal; Merhav, Goni; Shifrin, Alla; Stein, Polina; Shelly, Shahar (Frontiers in Neurology, 2024)
Background and Objectives: Primary CNS Vasculitis (PCNSV) is a rare inflammatory disorder that affects the blood vessels of the central nervous system. We aimed to analyze the neurological presentations, clinical follow up and long-term outcomes of patients with primary central nervous system vasculitis.We conducted a retrospective analysis of medical records to assess the neurological presentation. rate of remission, and the functional status at last follow-up in patients with primary central nervous system vasculitis seen in our center in the last 13 years (2010-2023).We identified five patients, median age at symptom onset 31 years (range 15-41 years), including four males (80%) from Muslim Arab (n=4) and Ashkenazi Jewish (n=1) backgrounds.Symptoms persisted for a median of 36 weeks (range 3 weeks to 4 years) before diagnosis, with one case exceeding three years. Follow-up lasted a median of 56 months (range 20-161 months). Clinical symptoms varied, presenting unilateral weaknesses (n=2), cognitive and gait abnormality (n=1), headaches (n=1), and epileptic seizures (n=1). MRI scans revealed abnormalities in the basal ganglia, corona radiata, parietal, and frontal lobes, showing hemorrhage, vasogenic edema, restricted diffusion, and enhancement post-gadolinium. All patients reported progressive holocephalic headaches and cognitive changes with overall progressive symptoms. Initial neurological examinations revealed abnormalities in all patients and included one or more of the following: cognitive or visual impairment, (n=2) seizures (n=1), and unilateral UMN signs (n=2). At first neurological examination All but one patient required walking aids including (cane 2, wheelchair, bedridden 1). Patients were stable (n=2), deteriorated (n=1) or improved (n=2). Two patients still required ambulatory aids, with one using a cane and the other using a wheelchair, while the remaining three did not require any ambulatory aids.The study on PCNSV highlights varied symptoms and diagnostic challenges, including delayed diagnosis and a spectrum of neurological issues from cognitive impairments to seizures.Brain biopsies showed lymphocytic infiltration, thrombi, and necrosis. Immunotherapy significantly improved clinical and radiological outcomes. Over 56 months of follow-up, outcomes varied from stability and deterioration to improvement.